Factors effects on e-learners’ satisfaction at the higher education institutions in Saudi Arabia - Ahmad, Ateeq; Padlee, Siti Falindah; Saadon, Mohd Saiful Izwaan (International Journal of Evaluation and Research in Education (IJERE), 2024)
To give e-learners enough freedom during their learning experiences, interactive learning, or “e-learning” as it is more commonly known, uses information and communication technologies. Because it provides e-learners with several benefits, e-learning has garnered a lot of attention in the education sector during the COVID-19 epidemic. This study’s primary goal is to assess how internet connection (ICS) and service quality (SVQ) affect e-learner satisfaction (ELS). This study assessed the effects of factors (service quality and internet connection) on e-learner satisfaction in Saudi Arabian higher education institutions. The investigation was carried out using a quantitative technique. Information was acquired from Saudi Arabian universities. A total of 350 questionnaires were reviewed. The relationship between factors (service quality and internet connection) and their effect on the satisfaction of e-learners was examined using structural equation modeling (AMOS SEM). The study’s results demonstrated that factors including SVQ and ICS have a positive effect on how satisfied e-learners are. This article recommends that responsible authorities pay special attention to ensuring quality and existing regulations and standards to address the issues that could affect ELS with e-learning in Saudi Arabian higher education institutions.